PERAN PUBLIC RELATION DALAM CSR “PROGRAM WASH” PT AQUA DANONE INDONESIA - Aprilia Nugraheni; Ahmad Toni (Universitas Prof. Dr. Moestopo (Beragama), 2022)
In the context of commercialization, corporate social responsibility (CSR) is an effort to build a positive image of the company through the role of Public Relations in the publication of CSR programs. One form of CSR program implementation carried out by PT Aqua Danone is WASH (Water Access, Sanitation and Hygine). This study aims to analyze the role of PR with the four - step method and the 3P concept in CSR . The qualitative method used in this research is through a descriptive approach. The research data obtained are documentary secondary data conducted by researchers on the website and social media of PT Aqua Danone, as well as interviews with the mass media. Data acquisition technology utilizes library research and observations on the Danone website and online news. As a result, the fact on the ground is that the need for clean water sanitation is very high in 18 districts, especially in watersheds (DAS) and post-disaster. Planning and programs are carried out in a participatory manner with the government, NGO partners and the community. Action and Communication is carried out with various parties and the media. The evaluation was carried out using the 3 P (Planet, People, Profit) concept, namely 120,000 beneficiaries, Badung, Bali and Kupang regencies, NTT received the title of Village Free of Open Defecation, and PT Aqua Danone earned a stable net income. This enhances a positive image for PT Aqua Danone so that it gets awards from the central and local governments